Ability of Lactobacillus plantarum JR64 isolated from noni juice in lowering Cholesterol in vivo - Lanjar Sumarno; Djumali Mangunwidjaja; Anas M. Fauzi; Khaswar Syamsu; Nastiti Siswi Indrasti; Bambang Prasetya (Chemical Engineering Diponegoro University, 2011)
Recently public’s attention to the importance of healthy food increases rapidly. Probiotic based food exploiting lactic acid bacteria is among the healthy food. Lactobacillus plantarum JR64 isolate from Morinda citrifolia fruit was assessed for its probiotic in-vivo by using Wistar Rat. The purpose of this research was to study the ability of probiotic Lactobacillus plantarum JR64 in lowering serum LDL (Low Density Lipoprotein) of Wistar Rat. Twenty Rats were grouped into 4, each group consisted of 5 Rats. First Group was a negative control given standard normal diet of 20 gr/day plus aquadest. Second Grup was a positive control given cholesterol normal diet 20 gr /day plus Propil Tio Urasil (PTU) 60 mg/kg body weight/day. Third Group was supplemented with normal diet 20 gr /day plus Propil Tio Urasil (PTU) 60 mg kg body weight /day and 1012 CFU Lactobacillus plantarum JR64. Fourth Group was the same as third Group unless the probiotic using commercial probiotic Lactobacillus bulgariccus at 1012 CFU. Blood samples were withdrawn for measurement of total cholesterol, triglyceride, High Density Lipoprotein (HDL), and Low Density Lipoprotein (LDL) cholesterol every week and measured by using spectrophotometer with 546 nanometers wavelength. The results show that probiotic Lactobacillus plantarum JR64 isolated from noni juice significantly (p < 0,01) reduce Low Density Lipoprotein (LDL) and Triglyceride in vivo and tend to reduce High Density Lipoprotein (HDL) and total cholesterol.